Performance of islamic banking in Malaysia : A comparative study - Noorsuriani, Binti Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study aims to revisit the performance of Malaysia’s Islamic banking which is based interest-free principle or principle of Profit-and-Loss (PLS) sharing during the financial crisis by extending pertaining period of 2006-2010 based on financial ratios. The study provides information on the issue of bank performance particularly during the pre and post–subprime crisis period of 2008. The study is looking at the examination of difference performance of local Islamic banks in comparison with foreign Islamic banks in Malaysia. And found that foreign Islamic banks are less profitable, less risky and more solvent, more liquid and also less efficient in compared to the local Islamic banks during the year 2006-2010. By applying t-test analysis to twelve financial ratios, this study exhibit that, there is a partially significant difference between independent variables and performance of local and foreign Islamic banks. Albeit, the study found that foreign Islamic banks is less profitable, less risky and more solvent, more liquid and also less efficient, however, the foreign Islamic banks is improving over time indicating convergence with the performance of the local Islamic banks.